The “House of Cards” of Political Reality / КАРТОЧНЫЙ ДОМИК ПОЛИТИЧЕСКОЙ РЕАЛЬНОСТИ - CHERNENKO JULIA A. / ЧЕРНЕНКО ЮЛИЯ АЛЕКСАНДРОВНА (Наука телевидения)
The article gives the narrative analysis of the women images of three television series that cover the political reality of USA — “Political Animals”, “Madame Secretary” and “House of Cards”. They have been chosen in connection to the indication of the possible sponsoring of them from Clinton. The author investigates the parallels between the screen reality of these television series and the current political reality of USA and one of its actors – presidential candidate for the 2016 election Hillary Clinton. The topicality of the research of reflections of political realities in the screen-related arts grows in consideration of the rising significance of the conception of “mediatization” of politics. Basing herself on the approaches towards “mediatization” and its effects, and also building her theory on the foundations of Russian researchers of literary subjects from the realm of literary studies and American researchers of “storytelling,”, the author gives a brief overview of the interaction between stories and screens through the history of human society. This kind of approach gives the author the ability to show how the screen realities and storytelling can have impact on current political reality in the era of “mediatization of everything” and “post-truth politics”. The following narrative analysis of female figures in the aforementioned television serials related to politics makes it possible to observe a strong embedment of feminist issues in the American screen culture. The author demonstrates and analyzes the features of the main heroines of the analyzed television series which make it possible to conclude about their similarity to the figure of presidential candidate from the Democratic Party for the 2016 election, Hillary Clinton. Those parallels include her political experience as the Secretary of State, of her husband being the former president of the USA (and the experience of being the first lady of the country), of her preference of women for her assistants in the electron campaign, as well as the general features of Hillary Clinton. Because it would not be possible to analyze the figure of the main heroine without analyzing a complex of characters from the serial movies, certain conclusions also relate to the general features of political reality reflected in the screen cultures – the latter may include examinations of the figures of Russia and the Islamic Caliphate as the political opponents of the USA in the “House of Cards” serial.